Basita Paribasa dalam Tembang Pop Bali sebagai Bentuk Pemertahanan Kearifan Lokal Bali - Ida Bagus Made Ludy Paryatna; Ida Bagus Putra Manik Aryana (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
This study aims to determine the basita paribasa in Balinese pop songs. Balinese pop songs are one of the means that are still consistent in the use of basita paribasa so that Balinese pop songs can be said to be a medium for maintaining local wisdom of basita paribasa. In this study, the selection of songs on the Ketut Bimbo album was limited by using a qualitative descriptive method. In the lyrics of Ketut Bimbo's songs on three albums, namely provocateur, playing bliyard, ipah-ipuh, containing paribasa cecangkitan, sesonggan, sesmbing, wewangsalan, sesemon, sesenggakan, sesawangan. Baribasa Bali in Balinese pop songs will affect the Balinese people in their use when communicating. This will have a positive impact on maintaining Balinese local wisdom in the field of language, namely the style of language commonly called basita paribasa as a beautification of the language of communication in society.